1995
DOI: 10.1246/bcsj.68.146
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregated Higher-Structure of 1,3 : 2,4-Di-O-benzylidene-d-sorbitol in Organic Gels

Abstract: 1,3 : 2,4-Di-O-benzylidene-d-sorbitol (d-DBS) can cause gelation of organic solvents of a wide range of polarity into a gel state. The aggregated structures of d-DBS/organic solvent systems were studied, mainly by using IR, UV, and circular dichroism (CD) spectroscopy. In the case of the racemate Dl-DBS, no gel state was formed. In IR spectra of d-DBS and Dl-DBS in the solid state, the intensities of νOH and νCO absorption in d-DBS were found to be larger than those in Dl-DBS. It is assumed that the hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 20 publications
7
59
3
Order By: Relevance
“…In further work, Yamasaki and co-workers selectively converted each of the 5-OH group and the 6-OH group into methoxy groups, 39 and observed that no gelation occurred when the terminal (6-OH group) was protected, while gelation still occurred with the 5-OH group protected. As such, they proposed that 6-OH is critical as a hydrogen bond donor for DBS self-assembly.…”
Section: Experimental and Computational Conceptsmentioning
confidence: 99%
“…In further work, Yamasaki and co-workers selectively converted each of the 5-OH group and the 6-OH group into methoxy groups, 39 and observed that no gelation occurred when the terminal (6-OH group) was protected, while gelation still occurred with the 5-OH group protected. As such, they proposed that 6-OH is critical as a hydrogen bond donor for DBS self-assembly.…”
Section: Experimental and Computational Conceptsmentioning
confidence: 99%
“…[6] We have used dibenzylidene sorbitol (DBS), which readily organises, at very low concentrations, into three-dimensional percolation networks in low-molecular-weight organic liquids. [7] DBS is also known to be an efficient clarifying agent for isotactic PP [8] but not for PE.…”
Section: Introductionmentioning
confidence: 99%
“…Different spectroscopies can be used specifically for a given gelator. For instance, if paramagnetism is involved, EPR can be used (19); if H-bonds participate in the aggregation mechanism, IR spectroscopy is instructive (20); if luminescence phenomena are implied, fluorescence is then useful (21)(22)(23). These techniques take advantage of the amplitude variation of a spectral feature of the system which is sensitive to the degree of aggregation of the gelator molecules.…”
Section: Introductionmentioning
confidence: 99%